A simple graphical model of small mammal succession after fire in the Brazilian cerrado - Henriques, Raimundo P. B.; Briani, Denis C.; Palma, Alexandre R. T.; Vieira, Emerson M. (Walter de Gruyter & Co, 2006)
We studied the succession of small mammal species after fire in the cerrado (Neotropical savanna) of Central Brazil. Populations of small mammals were sampled with live-trapping techniques in a series of nine sites of different successional age, ranging from 1 to 26 years after fire. Ten species of small mammals were captured through all the seral stages of succession. Species richness ranged from two to seven species by seral stage. The species were arranged in different groups with respect to abundance along the succession: the first was composed of early successional species that peaked <2 years after fire (Calomys callosus, C. tener, Thalpomys cerradensis, Mus musculus, Thylamys velutinus); the second occurred or peaked 2-3 years after fire (Necromys lasiurus, Gracilinanus sp., Oryzomys scoth). Gracilinanus agilis peaked in the last seral stage. Species richness of small mammals showed an abrupt decrease from an average of four species immediately after fire to two species 5-26 years after the last fire. We propose a simple graphical model to explain the pattern of species richness of small mammals after fire in the cerrado. This model assumes that the occurrence of species of small mammals is determined by habitat selection behavior by each species along a habitat gradient. The habitat gradient is defined as the ratio of cover of herbaceous to woody vegetation. The replacement of species results from a trade-off in habitat requirements for the two habitat variables.
Keywords: brazil; habitat selection; marsupials; model; rodent; savanna; species richness